Tapping into the 'standing-reserve': a comparative analysis of workers' training programmes in Kolkata and Toronto - Maitra, Saikat; Maitra, Srabani (Studies in continuing education, 2015)
This paper examines employment-related training programmes offered by state funded agencies and multinational corporations in Toronto (Canada) and Kolkata (India). In recent years both cities have witnessed a rise in the service sector industries aligned with global regimes of flexible work and the consequent reinvention of a worker subject that is no longer disciplined according to the needs of industrial production. A worker must now be self-regulated, competitive, flexible, with an ability to convey an urbane, English-speaking deportment within the workplace. Training of employees, especially soft skill training becomes crucial in this connection as a form of technology for achieving this end. Based on Martin Heidegger's conceptualisation of 'standing-reserve', we suggest that what training programmes do in the context of neoliberal capitalist production is the creation of an essential quality of human-ness that has to be harnessed, its potentialities tapped and amplified through training. We further suggest that such programmes often remain heavily influenced by race/class/gender hierarchies as well as stereotypical assumptions of desirable/undesirable bodies, forms of socialisation and modes of habitation that often are naturalised in the course of training.